Encyclopedia of industrial and organizational psychology - Rogelberg, Steven G.; Gale Group (Thousand Oaks, Calif. SAGE, 2007)
A thorough overview of the cross-disciplinary field of industrial and organizational psychology for students, researchers, and professionals in the areas of psychology, business, management, and human resources. In two volumes, readers are provided with state-of-the-art research and ready-to-use facts.
Editorial board -- List of entries -- Reader's guide -- About the editor -- Contributors -- Introduction -- Entries -- Volume I: A-L -- Volume II: M-W -- Appendixes -- Index.
"A Sage reference publication."
Electronic reproduction.
Keywords: Psychology, Industrial -- Encyclopedias; Organizational behavior -- Encyclopedias; Electronic books